Electrochemical cells - O'Brien, Michael; Newbyte Educational Software (Australia : Newbyte Educational Software, 2003)
This simulation software enable students investigate electrochemical cells in which they can change electrodes , salts , concentration and temperature . This simulation allows both qualitative and quantitative investigations
Keywords: Electrolytical cells -- Software